Pengaruh Sentra Bahan Alam Terhadap Kemampuan Sains Anak Pada Kelompok B Ra Roudlotul Mujtahidin Jrambe Kecamatan Dlanggu Kabupaten Mojokerto - Putri Ismawati; Iisnawati Iisnawati (Universitas Islam Lamongan, 2018)
This study aims to improve the ability of children science Group B RA Roudlotul Mujtahidin Jrambe Village District Dlanggu Mojokerto through Sentra Bahan Alam.Penelitian using quantitative research methods with the type of research is experimental research. This research uses Pre-Experimental Designs research design using One-Group Pre-Test-Post-Test Designs.The value of improvement of the Science Ability of the 26 students who have done the application of learning Material Sentra Nature average score or value increased 13.50. Test Statistics above Asymp value. Sig (2-tailed) is 0, Because the value of Asymp. Sig (2-tailed) is smaller than 0.005 then there is a significant effect of the development of children's Science Skills before and after the application of learning Material Sentra Nature. Judging from the analysis of statistical figures generated through Wilcoxon Test, the result is that the Application of Learning Center of Natural Resources has an effect on increasing the ability of children Science in RA Roudlotul Mujtahidin Jrambe. Learning Center Natural Materials is very effective to improve the development of Science Capabilities of children especially